UPAYA PENCEGAHAN STUNTING MELALUI EDUKASI DAN PENGOLAHAN PANGAN FUNGSIONAL BAGI WARGA DUSUN KRAPYAK KULON, PANGGUNGHARJO, SEWON, BANTUL - Sari, Eni Kartika; Dellima, Beta Ria Erika Marita (Kumawula: Jurnal Pengabdian Kepada Masyarakat, 2024)
Stunting is a growth disorder, metabolic disorder, brain development disorder, and affects children's intelligence. Until now, the problem of stunting still occurs in the community, including in Krapyak Kulon, Panggungharjo Village, Sewon, Bantul. On the other hand, natural ingredients that are quite often found in Panggungharjo Village are lemongrass and ginger, the use of which is not optimal even though they are rich in active ingredients. Therefore, efforts are needed to increase the use value of these ingredients, which in this case are ingredients for making functional food to prevent stunting. This service aims to increase knowledge about the dangers of stunting and alternative functional food to prevent stunting in the form of Sang Kukis. Sang Kukis is a cookie made from natural ingredients rich in nutrients, namely banana flour, green bean extract, ginger and lemongrass with an attractive shape for children. Service activities are carried out offline or face-to-face through counseling and direct practice in making Sang Kukis. Community knowledge was measured through a pretest before the activity and a posttest after being given counseling and practical food making practices by the service team. Based on the results of the pretest and posttest which were attended by 22 participants, it can be stated that there was an increase in respondents' understanding of the definition of stunting from 45.45% to 68.18%, material on understanding the characteristics of stunting from 50% to 81.81%, causes of stunting from 45.45%. % to 90.90%, understanding of the dangers of stunting from 40.90% to 90.90% and understanding of functional food processing to prevent stunting from 31.81% to 86.36%. Based on this data, it can be concluded that community service activities can increase public understanding about the dangers of stunting and alternative foods to prevent stunting.Stunting merupakan gangguan pertumbuhan, gangguan metabolisme, gangguan perkembangan otak, hingga mempengaruhi kecerdasan anak. Sampai saat ini, permasalahan stunting masih terjadi pada masyarakat termasuk di Krapyak Kulon, Desa Panggungharjo, Sewon, Bantul.  Di sisi lain, bahan alam yang cukup banyak ditemukan di Desa Panggungharjo adalah serai dan jahe yang pemanfaatannya belum optimal meskipun kaya kandungan bahan aktif. Oleh karena itu, perlu upaya peningkatan nilai guna bahan tersebut yang dalam hal ini menjadi  bahan pembuatan pangan fungsional pencegah stunting. Pengabdian ini bertujuan untuk meningkatkan pengetahuan tentang bahaya stunting dan alternatif pangan fungsional pencegah stunting berupa Sang Kukis. Sang Kukis adalah kukis yang terbuat dari bahan alam kaya nutrisi yaitu tepung pisang, ekstrak kacang hijau, jahe, dan serai dengan bentuk yang menarik untuk anak. Kegiatan pengabdian dilaksanakan secara offline atau tatap muka melalui penyuluhan dan praktik secara langsung pembuatan Sang Kukis. Pengetahuan masyarakat diukur melalui pre test sebelum kegiatan dan post test setelah diberikan penyuluhan dan praktik pembuatan pangan fungsional oleh tim pengabdi. Berdasarkan hasil pre test dan post test yang diikuti oleh 22 peserta, dapat dinyatakan bahwa terjadi peningkatan pemahaman responden tentang definisi stunting dari 45,45% menjadi 68,18%, materi pemahaman ciri stunting dari 50% menjadi 81,81%, penyebab stunting dari 45,45% menjadi 90,90%,  pemahaman bahaya stunting dari 40,90% menjadi 90,90% serta mengerti pengolahan pangan fungsional pencegah stunting dari 31,81%  menjadi 86,36%. Berdasarkan data tersebut dapat disimpulkan bahwa kegiatan pengabdian kepada masyarakat dapat meningkatkan pemahaman masyarakat tentang bahaya stunting dan alternatif makanan pencegah stunting.